STUDY OF LONG WEIGHT RELATION OF SCYLLA SERRATA IN MANGROVE FOREST AROUND THE WET LABORATORY FPIK EEAST LIKUPANG DISTRICT NORTH MINAHASA - Tumbel, Stivensian M.; Manu, Gaspar D.; Kambey, Alex D. (Sam Ratulangi University, 2018)
Mud crab (Scylla serrata) is a ten-legged crustacean animal from Brachura infraordo, known to have a very short tail (in Greek: brachy = short, ura = tail). Mangrove crab is one of the aquatic biota that has significant economic value and its life is strongly influenced by the existence of mangrove forest. The purpose of this study is to identify and analyze the relationship of weight and growth patterns of mangrove crab (Scylla serrata). Sampling is obtained by catching activities using fishing gear that is bubu (chang). Based on the results of research conducted in the area of Mangrove Forest around Wet Laboratory Faculty of Fisheries and Marine Sciences, Likupang Timur in August - September 2017. Mangrove crab (Scylla serrata) in the can through research obtained as many as 32 individuals.Keywords: Mangrove Crab (Scylla serrata), Long Weight Relation, Growth Pattern, East Likupang ABSTRAKKepiting bakau (Scylla serrata) adalah binatang anggota crustasea berkaki sepuluh dari infraordo Brachura, yang dikenal mempunyai ekor yang sangat pendek (dalam bahasa Yunani : brachy = pendek, ura = ekor). Kepiting bakau adalah salah satu biota perairan yang bernilai ekonomis penting dan kehidupannya sangat dipengaruhi oleh keberadaan hutan mangrove. Adapun tujuan dari penelitian ini yaitu untuk mengidentifikasi dan menganalisis hubungan panjang berat berserta pola pertumbuhan dari kepiting bakau (Scylla serrata). Pengambilan sampel diperoleh dengan melakukan kegiatan penangkapan menggunakan alat tangkap yaitu bubu (chang). Berdasarkan hasil penelitian yang dilakukan di Daerah Hutan Mangrove sekitar Laboratorium Basah Fakultas Perikanan dan Ilmu Kelautan, Likupang Timur pada bulan Agustus ? September 2017. Kepiting bakau (Scylla serrata) yang di dapat selama melalukan penelitian diperoleh sebanyak 32 individu. Kata Kunci : Kepiting Bakau (Scylla serrata), Hubungan Panjang Berat, Pola Pertumbuhan, Likupang Timur.